Synagogen in Göttingen Aufbrüche und Abbrüche jüdischen Lebens - Schaller, Berndt (7e1fd72f-7052-40f4-8edf-8b84ec6470b8, 2017)
The book "Synagogues in Göttingen: departures and ceasing of Jewish life," deals with the 700-year history of Jewish life in Göttingen and the various synagogues that have been existing since the beginning of the 14th Century. This is the 2nd, revised and expanded edition.